Comparative efficacies of calcium hypochlorite and peroxyacetic acid treatments in inactivating Salmonella enterica on alfalfa seeds and sprouts - Myung-Ji Kim; Murli Manohar; Wim Dejonghe; Jinru Chen (Applied Food Research)
Alfalfa sprouts have been linked to outbreaks of gastrointestinal infections worldwide, and control of Salmonella has been a challenge to the sprout industry. This study examined the efficacy of calcium hypochlorite and peroxyacetic acid treatments in inactivating Salmonella enterica on alfalfa seeds/sprouts (n = 160). Commercial alfalfa seeds (2 g/sample) inoculated with four individual strains of Salmonella at 2.75–4.14 log CFU/g were treated with calcium hypochlorite and peroxyacetic acid according to manufacturers’ instructions, and water-rinsed seeds served as controls. Treated seeds were sprouted on 1% water agar at 25 °C for 7 days, and Salmonella populations were determined before and after seed treatment and sprouting. Data were fit into the general linear model and analyzed using ANOVA. Fisher's LSD test separated the means (P ≤ 0.05). Treatments with calcium hypochlorite or peroxyacetic acid reduced the mean Salmonella population on alfalfa seeds by ≤ 3.3 log CFU/g before sprouting. Overall, sprouts from seeds treated with calcium hypochlorite or peroxyacetic acid had 4.85–4.99 and 4.67–4.78 log CFU/g lower Salmonella counts than the controls. The average populations of the four strains were significantly different. The study suggests that treatments with the two sanitizers could be used to improve the microbial safety of alfalfa seeds/sprouts.